Analisis Penerapan Pajak Pertambahan Nilai pada PT Sarana Aspal Nusantara - Sutomo, Hadi (Jurnal Ilmiah Akuntansi Kesatuan, 2019)
This resecarh was conducted with the aim to find out whether the application of Value Added Tax to the company is in accordance with applicable tax regulations. The research was carried out by analyzing the collection, calculation, payment and reporting of Value Added Tax. The data sampel used in this research is the VAT Report at PT. Sarana Aspal Nusantara for the periode of 2016 – 2017. The results showed that the company had implemented Value Added Tax in accordance with the applicable tax provisions. However there was still Correction to the noficication letter or monthly VAT report, while the occurrence of these corrections was due to several factors such as the replacement of tax invoice, cancelation of tax invoice, and other factors. Therefore for future research the analysis data related to the application of Value Added Tax must be expanded and not only limited to VAT Notification Letter but also to all matters that have relevance to Value Added Tax so that the research results are expected to be more optimal